Extensive functional redundancy in the regulation of Candida albicans drug resistance and morphogenesis by lysine deacetylases Hos2, Hda1, Rpd3 and Rpd31. Issue 4 (14th December 2016) - Li, Xinliu; Robbins, Nicole; O'Meara, Teresa R.; Cowen, Leah E.
Summary: Current treatment efforts for fungal infections are hampered by the limited availability of antifungal drugs and by the emergence of drug resistance. A powerful strategy to enhance the efficacy of antifungal drugs is to inhibit the molecular chaperone Hsp90. Hsp90 governs drug resistance, morphogenesis and virulence in a leading fungal pathogen of humans, Candida albicans . Our previous work with Saccharomyces cerevisiae established acetylation as a novel mechanism of posttranslational control of Hsp90 function in fungi. We implicated lysine deacetylases (KDACs) as key regulators of resistance to the most widely deployed class of antifungals, the azoles, in both S. cerevisiae and C. albicans . Here, we demonstrate high levels of functional redundancy among the KDACs that are important for regulating Hsp90 function. We identify Hos2, Hda1, Rpd3 and Rpd31 as the KDACs mediating azole resistance and morphogenesis in C. albicans . Furthermore, we identify lysine 30 and 271 as critical acetylation sites on  C. albicans Hsp90, and substitutions at these residues compromise Hsp90 function. Finally, we show that pharmacological inhibition of KDACs phenocopies pharmacological inhibition of Hsp90 and abrogates Hsp90‐dependent azole resistance in numerous Candida species. This work illuminates new facets to the impact of KDACs on fungal drug resistance and morphogenesis, provides important insights into the divergence of the C. albicans Hsp90 regulatory network and reveals new targets for development of antifungal drugs. Abstract : Here, we establish that Hsp90 is acetylated on lysine 30 and 271, and other residues to be identified, in the fungal pathogen Candida albicans. There is a large degree of functional redundancy between the KDAC complexes with Hos2, Hda1, Rpd3, and Rpd31 all being required to govern Hsp90‐dependent azole resistance. Cycling between acetylated and deacetylated states is important for orchestrating drug resistance, morphogenesis, and virulence.